A novel arthroscopic classification of deltoid ligament injuries in ankle fractures and its impact on surgical management - Pinto, Roberto Zambelli de Almeida; Dressler, Hugo Bertani; Pastor, Miquel Dalmau; Baumfeld, Daniel Soares; Castilho, Rodrigo Simões; Brandão Magalhães, João Murilo (Journal of the Foot & Ankle, 2026)
Introduction: Ankle fractures have an annual incidence of 0.1%-0.2% and may be associated with deltoid ligament injury in up to 58% of cases. The true prevalence and severity of these lesions may be underestimated when assessed using indirect diagnostic methods. Arthroscopy allows direct visualization of the intra-articular fascicles of the deltoid ligament, improving diagnostic accuracy. This study aimed to propose a novel arthroscopic classification of deltoid ligament injuries in acute ankle fractures and to analyze their association with Lauge-Hansen mechanisms. Methods: A prospective observational study was conducted at a tertiary hospital between January 2022 and March 2025. A total of 229 adult patients undergoing open reduction and internal fixation with arthroscopic assistance were included. Fractures were classified according to the Lauge-Hansen system (SAD, SRE, PAB, PRE). Deltoid injuries were graded arthroscopically as: Type 0 (intact); Type 1 (tibionavicular injury with partial pre- collicular tibiotalar lesion); Type 2 (tibionavicular plus pre- and collicular tibiotalar injury); and Type 3 (complete rupture involving the entire tibiotalar fascicle). Results: Mean age was 43.7 ± 15 years; 54.1% were male. Arthroscopic deltoid injury was identified in 42.8% (98/229). Among lesions, 31.6% were Type 1, 39.8% Type 2, and 28.6% Type 3. PRE fractures showed the highest injury rate (53.7%), followed by SRE (42.8%), PAB (28.6%), and SAD (12.5%). Increasing fracture-mechanism severity was significantly associated with a higher deltoid injury grade (coefficient = 0.395; 95% CI, 0.082-0.708; p = 0.013). Conclusion: Deltoid ligament injuries are common and more severe in complex rotational fracture mechanisms when assessed arthroscopically. The proposed novel arthroscopic classification provides an anatomy-based, progressive framework for medial instability and may support more precise intraoperative decision-making in the management of acute ankle fractures.